Customary Sanctions for Strengthening Moral Order and Social Harmony in South Sumatra Communities - Erniwati, Erniwati; Pertiwi, Hana; Asmita, Sri; Andriyani, Andriyani; Oktarina, Evi (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
The implementation of customary (adat) sanction-based strategies to minimise immoral acts illustrates the interaction between customary law, moral values, and social dynamics in local communities. This study aims to analyse the effectiveness of such sanctions in curbing immoral behaviour, which includes physical, verbal, and sexual offences outside of marriage, as well as other forms of social deviance. It examines the types of sanctions applied, such as fines, corporal punishment, forced marriage, and ostracism. From the perspective of Islamic law, these sanctions fall under ta'zir, a discretionary punishment used to uphold justice and maintain order. Based on family and social law theory, the study positions customary norms as tools for promoting collective morality and shaping social cohesion. Using a qualitative approach, data were collected through interviews with religious and traditional leaders, community elders, and young people, as well as through field observations. The findings show that customary sanctions foster awareness, promote moral conduct, and support social harmony by reinforcing shared ethical standards and encouraging communal responsibility. These practices are deeply embedded in cultural identity and often enjoy stronger legitimacy than formal legal mechanisms. Although not part of state law, customary sanctions operate as informal systems of justice and serve as culturally appropriate responses to moral decline. The significance of this study lies in its potential to inform policy and practice through culturally grounded strategies that integrate religious ethics, traditional values, and local wisdom. It also contributes to broader discourses on alternative dispute resolution, grassroots moral governance, and the role of local institutions in addressing youth immorality and sustaining social order.